Management of foot rot disease of black pepper with Trichoderma spp. - and M. ANANDARAJ, P.P. RAJAN, Y.R. SARMA (Indian Phytopathology, 2012)
Phytophthora foot rot of black pepper is one of the most serious production constraints. As part of the disease management, a number of Trichoderma isolates were isolated and screened both in vitro and in vivo. Five efficient isolates tested in the field were monitored and statistically analyzed for three years. There was reduction in the disease incidence over the years of study, where these isolates were applied. Isolates (T.virens-12 & T.harzianum-26) were found more effective to control the disease and isolate T.harzianum-26 most adaptive to the rhizosphere of black pepper as compared to other isolates.